Removal trends of typical priority control pollutants in wastewater treatment plant tailwater: Mechanisms clarifying and optimal process selection. (December 2022) - Xia, Xinhui; Liu, Yu; Li, Jianju; Zhao, Weixin; He, Shufei; Jiang, Junqiu; Zhao, Qingliang; Wei, Liangliang
Abstract: Priority control pollutants (PCPs) have attracted much attention due to their safety concerns during effluent recycling in wastewater treatment plants (WWTPs). To clarify the removal characteristics of typical PCPs in WWTP effluent, the removal rates of eight typical PCPs during coagulation, ozonation, ultrafiltration (UF) and their combined processes were investigated. Experimental results revealed that single advanced treatment could not efficiently remove all PCPs within the WWTP effluent, whereas the combined processes significantly improved the removal rates due to the synergy of different treatment units. Specifically, ATZ exhibited the highest removal efficiency of 72.45 % when the coagulation-ozonation progressed, owing to the strong attacking of ozone onto the reactive groups (CC bond, aniline, amido group). Similarly, >93.4 % of SMZ, DCF, NaP, and Ant were efficiently removed during the ozonation-UF treatment. By contrast, adsorption by membrane was the main reason for the excellent removal of BaA (95.32 %) during ozonation-UF process and BaP (96.28 %) in coagulation-UF treatment. The optimized selective strategies for different treatment processes for the above-mentioned eight PCPs reduction were proposed based on analytical hierarchical processes, and the simulation results revealed that: ozone oxidation and UF process were more feasible for the tertiary treatment of PCPs characterized by two rings linked by NH bonds, as well as those PAHs with three or more benzene rings; whereas coagulation-ozone and coagulation-UF were for PCPs with triazine rings and monocyclic aromatic compounds with carboxyl groups. Graphical abstract: Unlabelled Image Highlights: Almost 100 % PAHs were efficiently removed in UF related single/combined processes. Over 53 % of PCPs were reduced in coagulation-ozonation/UF combined processes. Analytic hierarchy process was applied to optimize advanced treatments selection. Ozonation-UF was recommended as the best choice to remove PCPs for landscape reuse.